Para rir e consumir?: a resposta do consumidor ao uso do humor na propaganda. - Resende, Karolina Cestari (2018)
Marketing professionals are looking for new and better ways to communicate with consumers, mainly because of the technological advances that have transformed the communication environment, bringing new challenges, opportunities and strategies (BELCH; BELCH, 2004). Among these strategies, it is observed the increasingly recurrent use of humor (STRICK et al., 2013). Thus, the objective of this research is to analyze how the use of humor in advertising influences in the consumer response. Therefore, three experimental studies were carried out, which underwent an evaluation process of the data collection instrument by specialists, the validation of the images and a pre-test before the application of online questionnaires. The Study 1 relates the use of humor or not in the image of an ad disclosed in a traditional media (magazine) and had 83 participants; while Study 2, answered by 93 interviewees, addresses the humor in an ad on Instagram. Finally, with 311 answers, Study 3 analyzes the use of humor in an advertisement disclosed in social network, however it follows a previous message with hedonic or utilitarian motivation and, instead of humor being present only in the image, it is also modified in the ad’s text. In the three studies, the dependent variables analyzed are: the Purchase Intention, the Attitude toward the Product and the Advertising Evaluation. The collected data were later treated using the SPSS and, for the analysis, it was used descriptive statistics using the mean, standard deviation, comparison of mean – T-Test and analysis of variance – ANOVA. The results indicate that there is not a single consumer reaction to humor in advertising, but the humor means were higher in the most of analyzes presented. The use of humor in ads disclosed in the magazine have a greater significance for the Attitude towards the Product than those advertised on Instagram. In addition, through the results of the third study, it was noticed that the participants have greater Purchase Intention and a more positive Attitude towards the Product when exposed to an advertisement preceded by an utilitarian message and with the humor present in the image in comparison to an ad in which the humor appears in the text - this for both approaches, utilitarian and humor in the case of Intention and, for the utilitarian scenario in the case of Attitude. Finally, regarding the evaluation of advertising in this third study, there were no cases in which humor was significant.